Verso una rinnovata dottrina strategica della Nato - De' Robertis, Anton Giulio (Rivista di studi politici internazionali, 2010)
<!–[if gte mso 9]> Normal 0 14 false false false IT X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> In front of the ever changing international political environment Nato is updating again, after ten years, its strategic doctrine through a process of consultations and analysis carried on by a the special group of experts named by its Secretary general. The widening of the spectrum of threats for the Western societies and the effort to ensure security and preserve stability requires the streamlining of the decision making of the Alliance and the deepening of the cooperation with the international actors which are part of the network established by Nato. A comprehensive approach, mixing military and civilian resources, is suggested in the implementation of missions, in order to win also the peace at the end of military operations. The recalled indivisibility of the European security involves a renewed engagement of Russia and the adoption of a real ‘joint action’ practice, as stated in the two agreements already entered with Moscow. This article introduces the concept of sustainable stability, achievable trough the practice of balance of the interest in the European as well as in the international system. En face de la constante évolution de l’environnement politique internationale, l’Otan est en train de mettre à jour, après dix ans, sa doctrine stratégique moyennant un processus de consultations et d’analyse développé par un groupe spécial d’experts nommé par son Secrétaire général. L’élargissement du spectre des menaces qui pèsent sur les sociétés occidentales et l’effort pour assurer la stabilité nécessitent de simplifier le processus décisionnel de l’Alliance et d’approfondir la coopération avec les acteurs internationaux du réseau établi par l’Otan. Une approche globale, le mélange des ressources militaires et civiles dans la mise en oeuvre des missions, est proposée afin de gagner également la paix après la fin des opérations militaires. L’indivisibilité de la sécurité européenne rappelée par les experts implique un engagement renouvelé avec la Russie et l’adoption d’une pratique réelle d’‘action conjointe’, comme indiqué dans les deux accords déjà conclus avec Moscou. Cet article introduit le concept de stabilité soutenable, qui serait possible grâce à la création et au respect d’un équilibre d’intérêt dans le système Européen aussi bien que international. PAROLE CHIAVE: Alleanza atlantica; Sicurezza; Stabilità sostenibile; Partnership atlantica; Relazioni Nato-Russia